2001
DOI: 10.1161/01.cir.103.9.1198
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variation in ABCA1 Is Associated With Altered Lipoprotein Levels and a Modified Risk for Coronary Artery Disease

Abstract: These data suggest that common variation in ABCA1 significantly influences plasma lipid levels and the severity of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
213
6
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 25 publications
17
213
6
6
Order By: Relevance
“…To our knowledge, no previous study has reported the prevalence of ABCA1 gene mutations in a population with low HDL-C. Our results may be interpreted to mean that mutations in the ABCA1 gene, which have been found in patients with TD and FHA, are not present to a high degree in the general population with low HDL-C. This has also been suggested previously by Clee and coworkers (10,11 ). A weakness of the current study is in limiting the screening to only 7 of the initially described mutations, whereas Ͼ30 mutations have now been reported in the ABCA1 gene (4 -9 ).…”
Section: To the Editorsupporting
confidence: 87%
“…To our knowledge, no previous study has reported the prevalence of ABCA1 gene mutations in a population with low HDL-C. Our results may be interpreted to mean that mutations in the ABCA1 gene, which have been found in patients with TD and FHA, are not present to a high degree in the general population with low HDL-C. This has also been suggested previously by Clee and coworkers (10,11 ). A weakness of the current study is in limiting the screening to only 7 of the initially described mutations, whereas Ͼ30 mutations have now been reported in the ABCA1 gene (4 -9 ).…”
Section: To the Editorsupporting
confidence: 87%
“…These findings have established that inefficient RCT by HDLs is a causal factor in atherogenesis in such individuals. However, because ABCA1 transporter mutations are rare and a common genetic variation at the locus contributes only slightly to typical variations in HDL-cholesterol (25,26 ), they provide no guidance on the extent to which RCT underlies the association between HDL-cholesterol and CHD in the general population. To address this question, we have tested by case-control study the hypothesis that clinically manifested CHD is associated more strongly with pre-␤-HDL concentration than with HDL-cholesterol in Japanese men.…”
mentioning
confidence: 99%
“…Several common polymorphisms have been reported in the coding and promoter regions of the ABCA1 gene [25,26]. Some are associated with altered plasma lipid levels and with the development of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the R219K polymorphism is associated with progression of atherosclerosis and with elevated triglyceride (TG) and HDL-C levels in familial hypercholesterolemia patients from Spain [27]. Other single-nucleotide polymorphisms in the coding region had milder effects on plasma lipids and atherosclerosis [25].…”
Section: Introductionmentioning
confidence: 99%